A review of the genus Evonima Walker, 1865 from China with description of a new species (Lepidoptera, Nolidae, Nolinae) - Hu, Yan-Qing; Yu, Yong; Huang, Zhen-Fu (Zootaxa, 2020)
Ten Chinese species of the genus Evonima Walker, 1865 are reviewed. A new species (Evonima tianmuensis sp. nov.) is described from Tianmushan Mt., Prov. Zhejiang. Adult and distribution of each species from China are illustrated. A key to species of the genus from China is provided.